(3GdEbJUGO GdfbOj hCShGb QCS GdeGd (B: s (3ehLgI dWdHI GdSfI GdKGfjI djSGfS JNUU(B: (3eGdjI h eMGSHI (B/ s - (3GdYeQj, UajIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3GdGWGQ GdfXQj h GdeaGgjej ddfbhO , GdGfXeI h GdbhGYO GdfbOjI ,GdfXQjGJ GdfbOjI , HfjI GdcJdI GdfbOjI h ebGHdGJgG , GdHfhc GdJLGQjI h GdhSGWI GdeGdjI , GdHfhc GdeQcRjI h GOGQI GdSjGSI GdfbOjI , GdfXGe GdeUQaj h GUdGMGJ GdSjGSI GdfbOjI aj GdLRGFQ , GdGShGb GdeGdjI , GdGShGb GdfbOjI , CShGb QGj GdeGd , CShGb QDhS GdCehGd GdOhdjI , s
(3GdeQGLY U(B. 122s
Keywords: (3CShGb GdeGds; (3GdGbJUGO GdeGdjs